Correction: Measuring Physical Functioning Using Wearable Sensors in Parkinson Disease and Chronic Obstructive Pulmonary Disease (the Accuracy of Digital Assessment of Performance Trial Study): Protocol for a Prospective Observational Study - Debbie de Graaf; Nienke M de Vries; Tessa van de Zande; Janneke J P Schimmel; Sooyoon Shin; Nathan Kowahl; Poulami Barman; Ritu Kapur; William J Marks Jr; Alex van 't Hul; Bastiaan R Bloem (JMIR Research Protocols)
In “Measuring Physical Functioning Using Wearable Sensors in Parkinson Disease and Chronic Obstructive Pulmonary Disease (the Accuracy of Digital Assessment of Performance Trial Study): Protocol for a Prospective Observational Study” (JMIR Res Protoc 2024 May 7:13:e55452) the authors noticed that one of the authors was not named correctly.